DOES PROBLEM-BASED LEARNING IMPROVE CRITICAL THINKING SKILL? - Bagus Shandy Narmaditya; Dwi Wulandari; Siti Rosnita Binti Sakarji (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: The study aims to understand the implementation of Problem-Based Learning and its impact on critical thinking skills for senior high school students. The study used the lesson study approach that was conducted in four cycles. Each learning activity consisted of identifying topic, presenting the report, and evaluating the Problem-Based Learning. The subject of the study was in a Senior High School in Malang, Indonesia. The level of critical thinking refers to Structure Observed Learning Outcome (SOLO) Taxonomy, consisting of Prestructural, Unistructural, Multistructural, Relational, and Extended Abstract thinking levels. The findings in the learning process show that the students’ critical thinking skills has increased. It is revealed by improving the ability to solve problems and making conclusions through critical thinking processes. The implementation of Problem-Based Learning also encourages students to think critically in the form of questioning, discussing problems and making solutions related to the employment issues, national income and economic growth in Indonesia. Keywords: Problem-Based Learning, Critical Thinking Skills, Lesson Study APAKAH PROBLEM-BASED LEARNING DAPAT MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS? Abstrak: Penelitian ini bertujuan untuk mengetahui penerapan Problem-Based Learning dan pengaruhnya terhadap kemampuan berpikir kritis pada siswa sekolah menengah atas. Penelitian ini menggunakan pendekatan lesson study yang dilakukan melalui empat siklus. Setiap aktivitas pembelajaran terdiri dari mengindentifikasi permasalahan, mempresentasikan laporan kegiatan, dan mengevaluasi pelaksanaan Problem-Based Learning. Subject penelitian ini dilakukan pada sebuah Sekolah Menengah Atas di Malang, Indonesia. Tingkat kemampuan berpikir kritis siswa dalam penelitian ini mengacu pada taksonomi SOLO (Structure Observed Learning Outcome) yang meliputi prastruktural, Unistruktural, Multistruktural, Relasional, and Extended Abstract. Hasil penelitian ini menunjukkan bahwa selama proses pembelajaran, kemampuan siswa dalam berpikir kritis telah meningkat. Hal ini ditunjukkan dari peningkatan kemampuan menyelesaikan masalah dan membuat kesimpulan melalui proses berpikir kritis. Penerapan Problem-Based Learning juga mendorong siswa memiliki kemampuan berpikir kritis dalam berbagai aktivitas seperti mengajukan pertanyaan, mendiskusikan permasalahan, dan membuat solusi terkait permasalahan pengangguran, pendapatan nasional, pertumbuhan ekonomi di Indonesia. Kata Kunci: Problem-Based Learning, Kemampuan Berpikir Kritis, Lesson Study